Status Daya Dukung Lahan untuk Keberlanjutan Pangan di Kabupaten Klungkung - Nyoman Sudipa (Institut Pertanian Bogor, 2021)
Land is an essential component for the sustainability of human life. Population growth and urbanization affect the availability of land in an area. Therefore, the land never increases, but the need for land continues to grow every year, converted to housing and other facilities. As an area that continues to develop, Klungkung Regency has decreased the availability of land due to development and investment activities, especially tourism investment and the construction of other supporting facilities for tourism and regional development. Therefore, the availability of land in Klungkung Regency continues to experience pressure, which impacts the ability to provide food. This study aims to determine land requirements, land availability, and land carrying capacity status in Klungkung Regency, which the policy-makers can consider to support food sustainability in Klungkung Regency. This study uses a quantitative approach using primary data from direct observations in the field and secondary data from government and previous research. The results show that the carrying capacity of land in the Klungkung Regency is in deficit based on the projections for 2021 to 2030. In overcoming the land deficit, it is necessary to increase land productivity by using land effectively and technology transfer to increase food productivity. Keywords: carrying capacity, food sustainability, Klungkung Regency land conversion